A Cascaded Droplet Microfluidic Platform Enables High‐Throughput Single Cell Antibiotic Susceptibility Testing at Scale. Issue 1 (8th December 2021) - Zhang, Pengfei; Kaushik, Aniruddha M.; Hsieh, Kuangwen; Li, Sixuan; Lewis, Shawna; Mach, Kathleen E.; Liao, Joseph C.; Carroll, Karen C.; Wang, Tza‐Huei
Abstract: The global threat of antibiotic resistance underscores critical but unmet needs for rapid antibiotic susceptibility testing (AST) technologies. To this end, droplet microfluidic‐based single‐cell AST offers promise by achieving unprecedented rapidity, but its potential for clinical use is marred by the capacity of testing one to few antibiotic conditions per device, which falls short from the required scale in clinically relevant scenarios. To lift the scalability constraint in rapid single‐cell AST technologies, a new cascaded droplet microfluidic platform that can streamline bacteria/antibiotic mixing, single‐cell encapsulation within picoliter droplets, incubation, and detection in a continuous, assembly‐line‐like workflow is developed. The scalability of the platform is demonstrated by generating 32 groups of ≈10 000 droplets with custom antibiotic conditions within a single device, from which a new statistics‐based method is used to analyze the single cell data and produce clinically useful antibiograms with minimum inhibitory concentrations in ≈90 min for the first antibiotic, plus 2 min for each subsequent antibiotic condition. Potential clinical utility of this platform is demonstrated by testing three clinical isolates and eight urine specimens against four frequently used antibiotics, and 100% and 93.8% categorical agreements are achieved compared to laboratory‐based results that became available after 48 h. Abstract : Single‐cell antibiotic susceptibility testing (AST) technologies have demonstrated unprecedented speed, but their clinical utility remains limited as most use devices that test only one concentration of one antibiotic. Here, a cascaded, assembly line‐like droplet microfluidic platform is developed to perform single‐cell AST against multiple antibiotics at the clinically relevant scale, thereby bringing single‐cell AST technologies a step closer to clinical settings.